Stratification of diabetic foot risk in adults with diabetes mellitus - Santos-Flores, Jesús Melchor (Universidad de Sonora, 2019)
Introduction: Diabetic foot is one of the most serious complications of diabetes mellitus; this is one of the most important chronic degenerative diseases in Mexico, since there are 6.4 million diabetics representing 9.2% of the adult population, they are exposed to develop complications of this nature. Objective: The objective of this study was to know and stratify the risk of diabetic foot in people with Type 2 Diabetes Mellitus according to age and sex, hospitalized in a second level institution in Sabinas Hidalgo, Nuevo Leon, Mexico. Material Methods: The design was descriptive transversal with a sample of 21 people (calculated from a population of 121 people), each participant was selected by simple random sampling. The data collection was carried out with the Diabetic Foot Assessment Scale with a Cronbachs alpha of 0.74. Results: The results were analyzed with the statistical package SPSS version 23 for Windows 10. It was found that 41.9% of the patients presented Moderate Risk, followed by those with High Risk (38.1%); likewise, men who were between the ages of 30 and 44 years old were the ones that showed the worse indicators that placed them in Moderate Risk. Further studies that include biochemical and cognitive variables from an ecological perspective are required.